Ideologi Pancasila: Doktrin yang Komprehensif atau Konsepsi Politis? - Wahyudi, Agus (Jurnal Filsafat "WISDOM", 2006)
The article consisted of controversial discussion on the status Pancasila. Its main problem is whther Pancasila maybe understood as an ideology or not. In this article, the solution in solving the controversial probelm is also offered. The transquality of the controversial status of Pancasila is actually easy to be carried out thourgh ideology and history of thought perspectives. Since the beginning of its history, such concept of ideology has interpreted into two forms of explanations; as a neutral or as a critical concept.The controversy of Pancasila's status, in the other sense is describing another aspect because of such two notions recommended a something a new perspective in elaborating. Pancasila is necessarily needed. It is argued in this article as separation between Pancasila's meaning as comprehensive doctrine with its meaning as a political conception. Finally, in this article, the benefit in expand Pancasila as a political conception is shown more than Pancasila as a comprehensive doctrine.